Setting up Flash CS5 for Android development - David, Matthew, 1971- (Visualizing the Web., 2011)
Learn how, as a Flash designer, you can set up a Flash CS5 environment to publish Android apps. Understand how to Design and develop for Android hardware Configure the Android SDK publish setting Set up Flash CS5 for Android Development Install your AIR application onto an Android OS Build your fist application for Android using Flash CS5 With the foundation built, you are now ready to focus on creating great AIR solutions with Flash CS5 for the Android platform.